2014
DOI: 10.1007/s10661-014-4103-0
|View full text |Cite
|
Sign up to set email alerts
|

Research on phosphorus loads and characteristics of adsorption and release in surface sediments of Nanyang Lake and Weishan Lake in China

Abstract: The characteristics of phosphate adsorption and the transformation of phosphorus forms in the release process of the sediments in Nanyang Lake and Weishan Lake are researched. Distribution of maximal amount of phosphorus adsorbed (Q max) is 112.76 and 93.91 mg kg(-1), respectively, and the adsorption processes of Nanyang Lake and Weishan Lake reach equilibrium after 48 h. Total maximal amount of phosphorus adsorbed is the amount of Q max and native adsorbed phosphorus (NAP). The m is the sum of the adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Regional differences in the petrographic type and the effective mineral quality of the phosphate rock has also inherently led to studies focusing on the formation conditions and mechanical properties of phosphate (Nguidi et al, 2021). Specifically, focus has been on the influence of the ancient geographical environment on the formation of inter-crystalline strength of the rocks (Priyank et al, 2015;Qin et al, 2015;Zhang et al, 2015;Han et al, 2016;Pan et al, 2017;Orlov et al,2020). These studies have shown that the basic mechanical behaviour of rocks is influenced by the mineral composition, structure type, and formation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Regional differences in the petrographic type and the effective mineral quality of the phosphate rock has also inherently led to studies focusing on the formation conditions and mechanical properties of phosphate (Nguidi et al, 2021). Specifically, focus has been on the influence of the ancient geographical environment on the formation of inter-crystalline strength of the rocks (Priyank et al, 2015;Qin et al, 2015;Zhang et al, 2015;Han et al, 2016;Pan et al, 2017;Orlov et al,2020). These studies have shown that the basic mechanical behaviour of rocks is influenced by the mineral composition, structure type, and formation conditions.…”
Section: Introductionmentioning
confidence: 99%